CONCRETES WITH BIOCHAROL FOR SUSTAINABLE CONSTRUCTION - Mazurak О.; Mazurak А.; Marushchak У.; Rehush А.; Mazurak Т.; Mazurak Р. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
Biochar (BC) additives in concrete have a high potential for use, both due to their environmental friendliness and their improved properties. The review highlights the aspects of using various biochar additives in concrete, characterizes biochar production methods and the influence of multiple factors on the quality of biochar materials. The physicochemical properties of bioconcretes, their composition, properties and problems associated with traditional production methods are presented. The advantages of biochar in concrete include the ability to be potential carbon absorbers and a binder substitute, as well as improving strength indicators, operational characteristics (durability, thermal insulation properties, fire resistance and frost resistance). This scientific work considers the process of forming concrete, focusing on the processes of forming a concrete matrix with biochar. The study analyzes the methodology for introducing biochar into the concrete matrix, criteria for selecting raw materials, component mixing protocols and procedures for controlling the quality characteristics of the final product. The processes of hydration and structure formation of cement stone with a biocomponent are considered. Examples of research on concrete compositions with a biochar component, their hardening conditions and construction and technical properties of the resulting bioconcretes are given. Particular attention is paid to the assessment of environmental aspects of the use of "green concretes" with biochar based on biowaste of plant origin, including their environmental profile, economic feasibility, life cycle analysis, as well as the real potential for reducing greenhouse gas emissions. The review also covers existing problems, predicted development directions and potential areas for future research in the context of biochar concrete components. The SCS bioconcrete certification system, according to the European standard EWC, is given. The presented comprehensive analysis provides a detailed understanding of the properties, production technology and environmental significance of biochar cement composites and concrete systems, serving as a guideline for further progress in the field of ecological materials science, construction and the development of the circular economy.